Catalisadores de platina suportada em nióbia para oxidação seletiva de CO - SELOX - Costa, Nathália Tavares (2016)
Brazil is the main producer of niobium in the world, but all this wealth is poorly used. Nb materials are promising in various reactions of industrial interest, including catalytic applications. In this study, we investigated the catalytic activity of Pt materials supported micro (Nb2O5) and nanostructured (Nb2O5-nano) niobia in the selective oxidation reaction of CO (SELOX). X-ray diffraction, temperature programmed reduction electron microscopy and spectroscopy in the infrared region have been decisive for the presence of different sites in the platinum catalysts. For Pt/Nb2O5, it was seen that there is competition between the CO and O2 Pt0 sites. The low catalytic activity of Pt/Nb2O5 and Pt/Nb2O5-nano were related to the difficulty of removing the CO molecules linearly adsorbed on Pt and with the presence of few active sites exposed, respectively. In the kinetic study carried out to Pt/Nb2O5, it was found that the effect of the partial pressures of O2 and CO on TOFCO varies with the temperature and concentrations of reactants and TOFCO2 is smaller than TOFH2O. Although none of the three models tested proved fully adequate understanding of the results, it was possible to propose a reaction route to SELOX reaction Pt catalysts supported on niobia, under the conditions studied.